Case histories in international politics - Stiles, Kendall W. (Pearson, 2013)
Case Histories in International Politics presents 20 original case studies to offer a historical perspective for better analyzing world affairs. Providing in-depth historical illustrations of core concepts in international relations, this casebook surveys major events in the 20th and 21st centuries and highlights both enduring and emerging problems. Case Histories in International Politics looks beyond current events to help readers make meaningful comparisons between what happened in the past and what is happening now.